Gestational age and socioeconomic status as mediators for the impact of prenatal alcohol exposure on development at 6 months. Issue 12 (31st October 2018) - Coles, Claire D.; Kable, Julie A.; Granovska, Irina V; Pashtepa, Ala O.; Plotka, Larisa D.; Dolhov, Victor B.; Wertelecki, Wladimir; Jones, Kenneth L.; Chambers, Christina D.; ,
Abstract: Background: Of the many negative outcomes associated with gestational alcohol use, one that has received relatively little attention is preterm birth and its possible contribution to effects of prenatal alcohol exposure (PAE) on development. To examine the increased risk for premature delivery associated with PAE and the joint influence of preterm birth and alcohol on child outcomes, analysis was carried out in a longitudinal cohort recruited in Western Ukraine. Methods: Alcohol‐using women and low or nondrinking controls were identified prenatally for a clinical trial of multivitamins and minerals (MVM) in ameliorating effects of PAE. Women were interviewed to provide information about medical and social status and other drug use. At delivery, information was collected about infant (N = 686) status including gestational age (GA) in weeks. Finally, 441 infants were followed to 6 months of age and cognitive (Mental Developmental Index [MDI]) and motor development (Psychomotor Developmental Index [PDI]) (measured using the Bayley Scales of Infant Development, second Ed (BSID‐II). Results: Seven percent infants were born at <37 weeks GA. The odds ratio for preterm delivery for Alcohol Exposed versus Low/No Alcohol was 2.6 (95% Confidence Interval 1.37, 4.94) ( p < .003); MVM supplements were associated with a lower rate of preterm delivery overall, but the relative proportion of preterm births did not vary by MVM supplement status between alcohol exposure groups. In mediation models of 6 month cognitive and motor development with reference to Barron and Kenney in 1986, GA significantly mediated alcohol effects (MDI: Z = −2.64, p < .008; PDI: Z = −2.35, p < .02) although PAE independently affected both outcomes (MDI: t = −5.6, p < .000; PDI: t = −3.19, p < .002). Conclusion: Results suggest that PAE is associated with higher rates of preterm birth and that alcohol's effect on development in infancy may be both direct and mediated by shortened length of gestation.